Communication Education and International Audiences: Reflections on Instructional Challenges and Pedagogical Strategy - Campbell, Heather; Strawser, Michael G.; George, Stephen (Journal of International Students, 2016)
As the movement toward international education continues, institutions must be proficient when reaching and teaching international students. Instructors should engage unique learning styles, address individual student needs, and take part in additional training to effectively teach international student learners. These instructional imperatives are especially important in communication related classes, like public speaking or composition. Throughout this reflection we briefly address the current landscape of the globalized western classroom and discuss current pedagogical challenges in communication courses from the perspective of communication instructors.